Acceso a medidas de acción afirmativa de las personas con discapacidad visual de la asociación APROPDVIMOS, en el cantón Morona, en el periodo 2022-2023. - Jaramillo Aguayo, Rosio Leonor (2023)
This research centers on the development of an approach that views the human being as a subject of rights in the pursuit of dignity for individuals with visual impairments. It employs affirmative actions as analytical tools to promote a perspective of social inclusion. The objective of this study is to analyze affirmative action measures targeted at individuals with visual disabilities. To achieve this objective, a qualitative and exploratory methodology was employed. The research utilized in-depth interviews and focus groups with members of the APROPDVIMOS Association in the Morona canton, as well as public sector employees from the same area. The results revealed dissatisfaction with the feasibility of public policies, highlighting economic, infrastructure, and access barriers experienced by both users and employees. Criticisms of the educational, healthcare, and employment systems were also evident, as they lacked effective inclusion processes, which had repercussions on the quality of life of this population. In conclusion, this study underscores the absence of a comprehensive, holistic, and long-term model for addressing the needs of priority groups, such as individuals with disabilities.